Determination of aflatoxin in processed dried cassava root: validation of a new analytical method for cassava flour - Gnonlonfin, G.J.B.; Katerere, D.R.; Adjovi, Y.C.S.; Brimer, L.; Shephard, G.S.; Sanni, A. (2010)
A new method that uses HPLC with a photochemical reactor for enhanced detection was developed and validated for the determination of aflatoxins in cassava flour. Samples were spiked with a mixture of four aflatoxins at 5, 10, and 20 microg/kg mixed with either 1 or 5 g NaCI and extracted with methanol-water (80 + 20, v/v) by shaking for 10 or 30 min. An immunoaffinity column was used for cleanup. HPLC with postcolumn derivatization, for enhancement of aflatoxin fluorescence, and fluorescence determination were used for quantitation of the toxin concentration. The method was validated for recovery, linearity, and precision at the three concentrations tested. Recovery ranges were 52-70, 69-85, and 80-89% for the spiking levels of 5.0, 10.0, and 20.0 microg/kg, respectively. It appears that the amount of salt (NaCl) and the shaking time are critical factors in this method; optimal performance was obtained when 1 g salt was used and the shaking time was 10 min. The good linearity and precision of the method allowed baseline separation from interferences, e.g., coumarins.